2011
DOI: 10.1111/j.1464-5491.2011.03443.x
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c 3 months after diagnosis predicts premature mortality in patients with new onset type 2 diabetes

Abstract: Our retrospective analysis adds weight to evidence suggesting that referral rates for people with Type 2 diabetes are increasing rapidly and that mortality rates are reducing but that the reasons for this are multifactorial. In addition to blood pressure, smoking and gender, the HbA(1c) achieved 3 months after the initial diagnosis also appears to predict subsequent mortality. It may be appropriate to consider early and intensive intervention for individuals with new onset type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Observational studies have demonstrated that hyperglycaemia is an important predictor of mortality and CVD risk [2][3][4][5][6][7][8][9][10][11][12][13][14][15], with the majority of studies showing positive linear relationships between HbA 1c and mortality or CVD risk [4,6,7,11,14,15]. However, several other important studies have suggested non-linear (U-or J-shaped) relationships [3, 5, 8-10, 12, 13, 16].…”
Section: Observational Studies Hba 1c and Mortalitymentioning
confidence: 99%
“…Observational studies have demonstrated that hyperglycaemia is an important predictor of mortality and CVD risk [2][3][4][5][6][7][8][9][10][11][12][13][14][15], with the majority of studies showing positive linear relationships between HbA 1c and mortality or CVD risk [4,6,7,11,14,15]. However, several other important studies have suggested non-linear (U-or J-shaped) relationships [3, 5, 8-10, 12, 13, 16].…”
Section: Observational Studies Hba 1c and Mortalitymentioning
confidence: 99%
“…All studies show an increase in allcause mortality with HbA1c values, where only the degree and pattern of association differ. Whilst most studies highlight a linear relationship [20][21][22][23][24][25][26][27][28][29], several studies report a J-or U-shaped relationship [30][31][32][33][34], indicating an increased all-cause mortality at lower HbA1c levels similar to that seen in the ACCORD trial.…”
Section: Introductionmentioning
confidence: 98%
“…Provision of appropriate tables and graphics [18][19][20][21][22][23] See also other supplementary tables…”
mentioning
confidence: 99%
“…Elevated HbA1c level has also been linked to a higher risk of diabetic retinopathy [48], nephropathy [49], cardiovascular diseases [50,51] and premature death [52,53]. Other studies must be done to establish the best cut point of A1C that correlates with specific diabetic microvascular complications, especially when the diagnostic tests are discordant.…”
Section: Resultsmentioning
confidence: 99%